NOWADAYS, PROBLEM AND SOLUTIONS OF THE AIR POLLUTION - Rahmonaliyeva Rahimaxon Mirzajon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Environmental pollution is not a new phenomenon, yet it remains the world’s greatest problem facing humanity, and the leading environmental causes of morbidity and mortality. Man’s activities through urbanization, industrialization, mining, and exploration are at the forefront of global environmental pollution. Both developed and developing nations share this burden together, though awareness and stricter laws in developed countries have contributed to a larger extent in protecting their environment. Despite the global attention towards pollution, the impact is still being felt due to its severe long-term consequences. This chapter examines the types of pollution—air, water, and soil; the causes and effects of pollution; and proffers solutions in combating pollution for sustainable environment and health.